Preceramic paper-derived Ti3Al(Si)C2-based composites obtained by spark plasma sintering - Krotkevich, D. G.; Kashkarov, E. B.; Syrtanov, M. S.; Murashkina, T. L.; Lider, A. M.; Schmiedeke, Samuel; Travitzky, Nahum (Ceramics International, 2021)
The paper describes the structure and properties of preceramic paper-derived Ti3Al(Si)C2-based composites fabricated by spark plasma sintering. The effect of sintering temperature and pressure on microstructure and mechanical properties of the composites was studied. The microstructure and phase composition were analyzed by scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. It was found that at 1150 °C the sintering of materials with the MAX-phase content above 84 vol% leads to nearly dense composites. The partial decomposition of the Ti3Al(Si)C2 phase becomes stronger with the temperature increase from 1150 to 1350 °C. In this case, composite materials with more than 20 vol% of TiC were obtained. The paper-derived Ti3Al(Si)C2-based composites with the flexural strength > 900 MPa and fracture toughness of >5 MPa m1/2 were sintered at 1150 °C. The high values of flexural strength were attributed to fine microstructure and strengthening effect by secondary TiC and Al2O3 phases. The flexural strength and fracture toughness decrease with increase of the sintering temperature that is caused by phase composition and porosity of the composites. The hardness of composites increases from 9.7 GPa (at 1150 °C) to 11.2 GPa (at 1350 °C) due to higher content of TiC and Al2O3 phases.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Composites; MAX-Phases; Mechanical properties; Microstructure; Preceramic paper; Spark plasma sintering